2020
DOI: 10.1021/acssuschemeng.9b07732
|View full text |Cite
|
Sign up to set email alerts
|

Novel Highly Branched Polymer Wood Adhesive Resin

Abstract: We propose a new idea for facile and green synthesis of urea-based highly branched polymers (HBPs) using polyamines and urea via deamination. More importantly, our strategy is to directly use the synthesized HBPs to construct plywood. The HBPs would be further condensed and solidified during the hot pressing process, resulting in the aldehyde-free wood adhesive with a high bonding performance. In this work, water-soluble HBPs were synthesized by one-pot and one-step strategy via polycondensations between urea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 34 publications
(46 reference statements)
2
48
0
Order By: Relevance
“…Low solids content and high viscosity are typical limitations associated with soy-based adhesives which negatively influence the flowability and gluability of the adhesive to decease their range of applications. , The solids content of the developed adhesives is given in Table . The solids content of SM-only adhesive is 26.92%, and this means that more water has to be evaporated from the adhesive and the wood veneer during the plywood manufacturing process, which lowers the production efficiency and bonding quality.…”
Section: Resultsmentioning
confidence: 99%
“…Low solids content and high viscosity are typical limitations associated with soy-based adhesives which negatively influence the flowability and gluability of the adhesive to decease their range of applications. , The solids content of the developed adhesives is given in Table . The solids content of SM-only adhesive is 26.92%, and this means that more water has to be evaporated from the adhesive and the wood veneer during the plywood manufacturing process, which lowers the production efficiency and bonding quality.…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of adhesive viscosity via introducing hyperbranched polymers has been the concern of numerous research studies by virtue of its highly branched 3D structure, low chain entanglement, versatile terminal functional groups, and brief synthetic route for the past decades. Beyond functioning in ensuring low viscosity, fine solubility, elevated reactivity, increased cross-linking sites, reduced formaldehyde emission level, additionally, free volume and internal cavities formed when the hyperbranched polymer is cross-linked with the target molecular structure will induce the cavitation effect, which can absorb energy under stress, so making the material more tough . Plenty of studies, including our previous work, , have demonstrated that the application of hyperbranched polymers in wood adhesives is feasible; herein, it is expected to be used to modify cellulose-based adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…42−44 Beyond functioning in ensuring low viscosity, fine solubility, elevated reactivity, increased cross-linking sites, reduced formaldehyde emission level, 45−47 additionally, free volume and internal cavities formed when the hyperbranched polymer is cross-linked with the target molecular structure will induce the cavitation effect, which can absorb energy under stress, so making the material more tough. 48 Plenty of studies, including our previous work, 45,49 have demonstrated that the application of hyperbranched polymers in wood adhesives is feasible; herein, it is expected to be used to modify cellulose-based adhesives.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Wood-based products, such as plywood, particleboard, fiberboard, and oriented strand board, are closely related to the everyday life of human beings. For example, furniture is used in every house and offices, and most furniture is an ensemble of different pieces of wood joined together with adhesives. , However, most of the adhesives used in wood products like furniture are formaldehyde-based chemicals, such as phenolic resin, urea formaldehyde resin, and melamine urea formaldehyde resin, which would release formaldehyde and other volatile organic compounds during the process of use. Because formaldehyde is a human carcinogen, people have to make a lot of efforts to get rid of formaldehyde emitted by furniture . Since formaldehyde release could be a life-long process for some furniture, the formaldehyde-based adhesives have loaded unneglectable harms to human beings.…”
Section: Introductionmentioning
confidence: 99%
“…For example, furniture is used in every house and offices, and most furniture is an ensemble of different pieces of wood joined together with adhesives. 1,2 However, most of the adhesives used in wood products like furniture are formaldehyde-based chemicals, such as phenolic resin, urea formaldehyde resin, and melamine urea formaldehyde resin, which would release formaldehyde and other volatile organic compounds during the process of use. 3−5 Because formaldehyde is a human carcinogen, people have to make a lot of efforts to get rid of formaldehyde emitted by furniture.…”
Section: ■ Introductionmentioning
confidence: 99%